Gut Microbiota Ecology and Inferred Functions in Children With ASD Compared to Neurotypical Subjects - Vernocchi, Pamela; Ristori, Maria Vittoria; Guerrera, Silvia; Guarrasi, Valerio; Conte, Federica; Russo, Alessandra; Lupi, Elisabetta; Albitar-Nehme, Sami; Gardini, Simone; Paci, Paola; Ianiro, Gianluca; Vicari, Stefano; et al. (Frontiers in Microbiology, 2022)
Autism spectrum disorders (ASDs) is multifactorial neurodevelopmental disorder. The communication between the gastrointestinal (GI) tract and the central nervous system seems driven by gut microbiota (GM). Herein, we provide GM profiling, considering GI functional symptoms, neurological impairment, dietary habits. Forty-one and 35 fecal samples collected from ASD and neurotypical children (CTRLs), respectively, (age range, 3-15 years) were analyzed by 16S targeted-metagenomics (V3-V4 region) and inflammation and permeability markers (i.e., sIgA, zonulin lysozyme), then correlated to subjects’ metadata. Our ASD cohort was characterized as follows: 30/41 (73%) with GI functional symptoms; 24/41 (58%) picky eaters (PEs), with one or more dietary needs), including 10/41 (24%) with food selectivity (FS); 36/41 (88%) presenting high and medium autism severity symptoms (HMASSs). Amongst the cohort with GI symptoms, 28/30 (93%) showed HMASSs, 17/30 (57%) were picky eaters and only 8/30 (27%) with food selectivity. The remaining 11/41 (27%) ASDs without GI symptoms were characterized by HMASS for 8/11 (72%) and 7/11 (63%) were picky eaters. GM ecology was investigated for overall ASD cohort versus CTRLs; ASDs with GI and without GI, respectively, versus CTRLs; ASD with GI versus ASD without GI; ASDs with HMASS versus low ASSs; PEs versus no-PEs; FS versus absence of FS. In particular, the GM of ASDs, compared to CTRLs, was characterized by increase of Proteobacteria, Bacteroidetes, Rikenellaceae, Pasteurellaceae, Klebsiella, Bacteroides, Roseburia, Lactobacillus, Prevotella, Sutterella, Staphylococcus and Haemophilus. In the comparison between ASD with GI symptoms versus CTRLs Sutterella, Roseburia, Fusobacterium were associated to ASDs. Interestingly, ASD with GI symptoms showed higher value of zonulin and lower levels of lysozyme, were also characterized by differentially expressed predicted functional pathways. Multiple machine learning models classified correctly the 80% of overall ASDs, compared with CTRLs, based on Bacteroides, Lactobacillus, Prevotella, Staphylococcus, Sutterella and Haemophilus features. In conclusion, in our patient cohort, regardless the evaluation of many factors potentially modulating the GM profile, the major phenotypic determinant affecting the GM, was represented by GI hallmarks and patients’ age .